2009
DOI: 10.1109/tmi.2009.2018112
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo High-ResolutionConductivity Imaging of the Human Leg Using MREIT: The First Human Experiment

Abstract: We present the first in vivo cross-sectional conductivity image of the human leg with 1.7 mm pixel size using the magnetic resonance electrical impedance tomography (MREIT) technique. After a review of its experimental protocol by an Institutional Review Board (IRB), we performed MREIT imaging experiments of four human subjects using a 3 T MRI scanner. Adopting thin and flexible carbon-hydrogel electrodes with a large surface area and good contact, we could inject as much as 9 mA current in a form of 15 ms pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…In vivo imaging has been tested in MREIT in some studies, for example (Kim et al, 2009) but no in vivo fMREIT studies have yet been tried. One advantage that fMREIT may have over ncMRI is that it may be possible to detect activity in complex neural architecture because contrast is controlled by a scalar rather than vector parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo imaging has been tested in MREIT in some studies, for example (Kim et al, 2009) but no in vivo fMREIT studies have yet been tried. One advantage that fMREIT may have over ncMRI is that it may be possible to detect activity in complex neural architecture because contrast is controlled by a scalar rather than vector parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these potential clinical applications, there are only a few in vivo MREIT studies reported (Muftuler et al 2006b, Kim et al 2008, Kim et al 2009). Probably the most important obstacle to the clinical application of MREIT is the limitation on the amount of electrical current that can be safely injected to a patient.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several investigators explored whether the IEC601 standards impose unnecessarily strict limits in impedance imaging experiments (Gilad et al 2007 and Kim et al 2009). Gilad et al (2007) suggested that this limit could possibly be increased up to 200μA for on-skin and 600μA for recessed electrodes for conductivity imaging of the head at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Since we mainly use carbon-hydrogel electrodes, the conductivity of hydrogel will be used as the reference value. 28 Using two projected current densities J ';P ; ' ¼ 1; 2, we will design an over-determined matrix system by linking the internal orthotropic conductivity value at each pixel to the known conductivity. To recover two unknowns of r 11 and r 22 , we will apply the dual-loop method.…”
Section: Introductionmentioning
confidence: 99%